Diversity Patterns of Protists Are Highly Affected by Methods Disentangling Biological Variants: A Case Study in Oligotrich (s.l.) Ciliates - Jiahui Xu; Jianlin Han; Hua Su; Changyu Zhu; Zijing Quan; Lei Wu; Zhenzhen Yi (Microorganisms, 2022)
Protists are a dominant group in marine microplankton communities and play important roles in energy flux and nutrient cycling in marine ecosystems. Environmental sequences produced by high-throughput sequencing (HTS) methods are increasingly used for inferring the diversity and distribution patterns of protists. However, studies testing whether methods disentangling biological variants affect the diversity and distribution patterns of protists using field samples are insufficient. Oligotrich (s.l.) ciliates are one group of the abundant and dominant planktonic protists in coastal waters and open oceans. Using oligotrich (s.l.) ciliates in field samples as an example, the present study indicates that DADA2 performs better than SWARM, UNOISE, UPARSE, and UCLUST for inferring diversity patterns of oligotrich (s.l.) ciliates in the Pearl River Estuary and surrounding regions. UPARSE and UNOISE might underestimate species richness. SWARM might not be suitable for the resolution of alpha diversity owing to its rigorous clustering and sensitivity to sequence variations. UCLUST with 99% clustering threshold overestimates species richness, and the beta diversity pattern inferred by DADA2 is more reasonable than that of the other methods. Additionally, salinity is shown to be one of the key factors responsible for variations in the community distribution of ciliates, but infrequent marine–freshwater transitions occurred during evolutionary terms of this group.